2008
DOI: 10.1080/10428190701742472
|View full text |Cite
|
Sign up to set email alerts
|

Frequency ofBCL2andBCL6translocations in follicular lymphoma: Relation with histological and clinical features

Abstract: Follicular lymphomas (FLs) usually carry BCL2 translocations although BCL6 translocations are also present. We explored relationships between translocations status and clinical or histological parameters at diagnosis in 182 patients stratified in four groups: BCL2-/BCL6-, BCL2+/BCL6-, BCL2-/BCL6+ and BCL2+/BCL6+. BCL2-/BCL6- and BCL2+/BCL6-. Double negative cases were ascribed to lower histological grades. In contrast, BCL2-/BCL6+ cases corresponded to higher grades. However, a majority of BCL2+/BCL6+ tumours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 26 publications
3
25
1
1
Order By: Relevance
“…39 It is also suggested that BCL6 rearrangements could be related to adverse clinical outcomes. 33,40 In our series, we observed that rearrangement in 21 cases (20%; n ¼ 105). DiazAlderete et al, 40 studying follicular lymphoma cases for BCL2 and BCL6 rearrangements by FISH on paraffin-embedded tissue sections, found positivity in 64 (101 þ /158) and 14% (22 þ /156) of the cases, respectively.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…39 It is also suggested that BCL6 rearrangements could be related to adverse clinical outcomes. 33,40 In our series, we observed that rearrangement in 21 cases (20%; n ¼ 105). DiazAlderete et al, 40 studying follicular lymphoma cases for BCL2 and BCL6 rearrangements by FISH on paraffin-embedded tissue sections, found positivity in 64 (101 þ /158) and 14% (22 þ /156) of the cases, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…33,40 In our series, we observed that rearrangement in 21 cases (20%; n ¼ 105). DiazAlderete et al, 40 studying follicular lymphoma cases for BCL2 and BCL6 rearrangements by FISH on paraffin-embedded tissue sections, found positivity in 64 (101 þ /158) and 14% (22 þ /156) of the cases, respectively. They also distributed their cases into four groups: BCL2 À /BCL6 À (32%), BCL2 þ / BCL6 À (56%), BCL2 À /BCL6 þ (5%), and BCL2 þ / BCL6 þ (9%).…”
Section: Discussionsupporting
confidence: 48%
“…It has been reported that 88.5% of bcl-2/IgH rearrangements occur at the MBR breakpoint (7). The results suggest a higher rate of BM infiltration than other studies (8)(9)(10).…”
Section: Discussioncontrasting
confidence: 55%
“…These data have been previously published. 12 Treatment protocols varied considerably within the series, over time, and among institutions. The protocols included 'watch and wait' approach, different regimens of chemotherapy, radiotherapy, and bone marrow transplantation as first-line therapy.…”
Section: Patientsmentioning
confidence: 99%